2014
DOI: 10.1038/ncomms6464
|View full text |Cite
|
Sign up to set email alerts
|

The role of maternal-specific H3K9me3 modification in establishing imprinted X-chromosome inactivation and embryogenesis in mice

Abstract: Maintaining a single active X-chromosome by repressing Xist is crucial for embryonic development in mice. Although the Xist activator RNF12/RLIM is present as a maternal factor, maternal Xist (Xm-Xist) is repressed during preimplantation phases to establish imprinted X-chromosome inactivation (XCI). Here we show, using a highly reproducible chromatin immunoprecipitation method that facilitates chromatin analysis of preimplantation embryos, that H3K9me3 is enriched at the Xist promoter region, preventing Xm-Xis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
70
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(77 citation statements)
references
References 39 publications
6
70
1
Order By: Relevance
“…Recently, Fukuda et al demonstrated that overexpression of Kdm4b, a histone demethylase for H3K9me3, can induce upregulation of Xist from the 4-cell stage in parthenogenetically activated embryos (Fukuda et al, 2014). This suggests, in fact, that global demethylation of H3K9me3 and subsequent alteration of the chromatin structure facilitate derepression of Xist on Xm otherwise repressed.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Fukuda et al demonstrated that overexpression of Kdm4b, a histone demethylase for H3K9me3, can induce upregulation of Xist from the 4-cell stage in parthenogenetically activated embryos (Fukuda et al, 2014). This suggests, in fact, that global demethylation of H3K9me3 and subsequent alteration of the chromatin structure facilitate derepression of Xist on Xm otherwise repressed.…”
Section: Discussionmentioning
confidence: 99%
“…The H3K9me3 mark is required to counteract the function of the Xist activator RNF12/RLIM on the Xm [41], which is deposited maternally in the oocyte and which is required for expression of Xist on the Xp during imprinted XCI [42]. However, it seems that H3K9me3 is not the primary imprinting mark, as there is no difference in H3K9me3 at the Xist promoter before and after oocyte growth, when the imprint is established [43].…”
Section: Imprinted XCImentioning
confidence: 93%
“…Like NANOG, PRDM14 binds to Xist intron 1 and the Rnf12 promoter in ESCs [47,84], where it represses Rnf12 by recruiting the PRC2 complex, which lies down the H3K27me3 mark. As RNF12 is essential for imprinted XCI [41,42] and gets downregulated in the epiblast [103], this could provide a mechanism, how Xist is repressed during XCR. A facilitating role in the XCR process in the blastocyst plays the Xist repressor Tsix, which becomes biallelically expressed in the epiblast during XCR [45,104].…”
Section: Resetting the Xci--stage By X--chromosome Reactivation (Xcr)mentioning
confidence: 99%
See 1 more Smart Citation
“…Little is known about the maternal imprint. Although de novo DNA methylation is dispensable (28), Xist's antisense partner, Tsix, plays a critical role in protecting the X M from silencing (29)(30)(31), and the H3K9me3 mark correlates with Xist silencing (32).…”
mentioning
confidence: 99%